A Case Study on Increasing Students' Awareness about the Educational Information Network (EBA) Platform - Ozan Coşkunserçe; Gökçe Becit İşçitürk (Anı Publishing, 2019)
The EBA (Educational Information Network), run by the Turkish Ministry of National Education, is an online platform for supporting the use of effective materials and providing training integration of technology using information technology tools wherever it is needed. Despite the large content offered by the EBA platform, it is thought that students are not getting enough benefit from the system. The purpose of this research is to determine what activities can be undertaken to improve the awareness of the platform and elimination of barriers that are faced by fifth grade students during the usage of the platform. For this purpose, following the promotional activities carried out in the 2016-2017 academic year, a questionnaire was applied to all students to gather data on EBA usage experience of students and semi-structured interviews with 16 students were conducted. According to research findings, 50% of the students had their first entry into the EBA system after the promotional activities and 61.7% of the students had increased the frequency of use of EBA after the promotional activities. In addition, it was seen that most of the students use EBA course module from the EBA modules. In the studies to be conducted for the promotion of EBA, the use of the model developed within the scope of the research is recommended.